Letter - Winstanley, E.
026-0009-001 Telegraphic Address: INLAND-"WHOLESALE, MANCHESTER." FOREIGN-"COPEXPORT, MANCHESTER." TELEPHONE: BLACKFRIARS 1212. EXTENSION NO. 87 PLEASE ADDRESS YOUR REPLY CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. CABLE CODES A.B.C. 6TH AND 7TH EDITIONS; WESTERN UNION 8 LETTER; BENTLEY COMPLETE PHRASE; BENTLEY SECOND PHRASE; A.1. MARCONI, AND PRIVATE. Our Reference: Export 2968 ST/JG. Your Reference: HVT/EAB. 23rd August, 1939. The Trades Union Congress, Transport House, Smith Square, LONDON. S.W.1. Dear Sirs, We acknowledge receipt of your letter of the 21st instant, reference HVT/EAB, informing us of the further packages which are going forward for shipment from Garston. If these arrive in time, they will be sent forward by the s.s. C.W.S. Progress, leaving to-night or to-morrow morning, and will be included on the same Bill of Lading as the other goods. We will advise you definitely in this regard in due course. Yours faithfully, E. Winstanley Export Department. 292/946/26/9